Slow molecular beams from a cryogenic buffer gas source - White,A; Popa,S; Mellado,Munoz J; Fitch,N; Sauer,B; Lim,J; Tarbutt,M (Physical Review Research, 2024)
We study the properties of a cryogenic buffer gas source that uses a low temperature two-stage buffer gas cell to produce very slow beams of ytterbium monofluoride molecules. The molecules are produced by laser ablation inside the cell and extracted into a beam by a flow of cold helium. We measure the flux and velocity distribution of the beam as a function of ablation energy, helium flow rate, cell temperature, and the size of the gap between the first and second stages of the cell. We also compare the velocity distributions from one-stage and two-stage cells. The one-stage cell emits a beam with a speed of about 82 m s¯¹ and a translational temperature of 0.63 K. The slowest beams are obtained using the two-stage cell at the lowest achievable cell temperature of 1.8 K. This beam has a peak velocity of 56 m s¯¹ and a flux of 9×10 ground state molecules per steradian per pulse, with a substantial fraction at speeds below 40 m s¯¹. These slow molecules can be decelerated further by radiation pressure slowing and then captured in a magneto-optical trap.